2004
DOI: 10.1080/01140671.2004.9514312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hand and chemical thinning on fruit size and quality of ‘Priana’ and ‘Beliana’ apricot(Prunus armeniaca)cultivars

Abstract: To cite this article: Levent Son (2004) Effects of hand and chemical thinning on fruit size and quality of 'Priana' and 'Beliana' apricot (Prunusarmeniaca) Annual apricot production is 100 000 t. The importance of the area is its earliness. This thinning study was carried out on 'Priana' and 'Beliana' apricot in 2002. In this experiment, 30%, 50%, 70% hand thinning; 1000, 1500, 2000 ppm carbaryl, and 10, 20, and 30 ppm naphthalene acetic acid (NAA) were applied. The main objective of this work was to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
6
11
0
1
Order By: Relevance
“…This data is in agreement with previous reports showed that application of NAA at 20 mg.l -1 (4 weeks AFB) was a good treatment for fruit thinning of apricot (Surányi, 1986;Bolat and Karlidağ, 1999;Son, 2004).…”
Section: Discussion Chemical Thinningsupporting
confidence: 93%
See 4 more Smart Citations
“…This data is in agreement with previous reports showed that application of NAA at 20 mg.l -1 (4 weeks AFB) was a good treatment for fruit thinning of apricot (Surányi, 1986;Bolat and Karlidağ, 1999;Son, 2004).…”
Section: Discussion Chemical Thinningsupporting
confidence: 93%
“…Flesh to nut ratio was the greatest in fruits treated with NAD. This data was in agreement with Son (2004) that stated 20 mg l -1 NAA had positive effects on flesh to nut ratio of 'Beliana' apricot.…”
Section: Discussion Chemical Thinningsupporting
confidence: 93%
See 3 more Smart Citations